2011
DOI: 10.1051/0004-6361/201117411
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneities in molecular layers of Mira atmospheres

Abstract: Aims. We investigate the structure and shape of the photospheric and molecular layers of the atmospheres of four Mira variables. Methods. We obtained near-infrared K-band spectro-interferometric observations of the Mira variables R Cnc, X Hya, W Vel, and RW Vel with a spectral resolution of about 1500 using the AMBER instrument at the VLTI. We obtained concurrent JHKL photometry using the the Mk II instrument at the SAAO. Results. The Mira stars in our sample are found to have wavelength-dependent visibility v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
69
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(89 citation statements)
references
References 21 publications
20
69
0
Order By: Relevance
“…4). photosphere (Wittkowski et al 2008(Wittkowski et al , 2011. Our VY CMa visibility curves show maxima near 2.25 μm and 1.70 μm, where the intensity of molecular bands is lowest.…”
Section: Observations and Data Reductionmentioning
confidence: 65%
“…4). photosphere (Wittkowski et al 2008(Wittkowski et al , 2011. Our VY CMa visibility curves show maxima near 2.25 μm and 1.70 μm, where the intensity of molecular bands is lowest.…”
Section: Observations and Data Reductionmentioning
confidence: 65%
“…We also want to compare the behavior of RSG stars and Mira stars, which also exhibit extended molecular layers (cf., e.g., Wittkowski et al 2011). We used the ratio of the observed visibilities in the continuum band (average between 2.27 and 2.28 μm) and the first (2−0) CO line at 2.294 μm as an observational indication of the contribution from extended atmospheric CO layers.…”
Section: Characterization Of the Extension Of The Molecular Atmospherementioning
confidence: 99%
“…Figure 10 shows the resulting ratios (V 2 cont /V 2 CO ) for our sources vs. log(L/L ) and ΔV, considering the RSGs by Wittkowski et al (2012), Arroyo-Torres et al (2013) Arroyo- Torres et al (2014). Results for Mira stars obtained by Wittkowski et al (2011) are also shown for comparison. Figure 11 shows the same visibility ratio but only for the RSG sample.…”
Section: Characterization Of the Extension Of The Molecular Atmospherementioning
confidence: 99%
See 2 more Smart Citations